2004
DOI: 10.1029/2003gl018659
|View full text |Cite
|
Sign up to set email alerts
|

Observations of transient luminous events (TLEs) associated with negative cloud to ground (−CG) lightning strokes

Abstract: [1] A balloon campaign was conducted in summer, 1999, to measure the stratospheric electromagnetic fields associated with sprites. Ground observations for detection of sprites included low light level TV (LLTV) observations from three sites. Flight 1 flew from Palestine, Texas at 01:14:31 UTC to 09:45:00 UTC on 07/06/1999. Flight 3 of the campaign flew from Ottumwa, Iowa at 00:39:32 UTC to 11:12:00 UTC on 08/21/99. During flight 3, 26 sprite halos associated with positive cloud-to-ground (+CG) strokes and 17 À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 16 publications
(34 reference statements)
4
31
2
Order By: Relevance
“…Halos are pancake‐like light‐emitting objects with diameters of ~80 km, occurring at altitudes of ~80 km [ Barrington‐Leigh et al ., ; Wescott et al ., ; Miyasato et al ., ; Bering et al ., ; Bering et al ., ; Frey et al ., ; Williams et al ., ]. Halos were initially thought to be elves by most ground observers using conventional cameras with 30 frames per second until Barrington‐Leigh et al .…”
Section: Introductionmentioning
confidence: 98%
“…Halos are pancake‐like light‐emitting objects with diameters of ~80 km, occurring at altitudes of ~80 km [ Barrington‐Leigh et al ., ; Wescott et al ., ; Miyasato et al ., ; Bering et al ., ; Bering et al ., ; Frey et al ., ; Williams et al ., ]. Halos were initially thought to be elves by most ground observers using conventional cameras with 30 frames per second until Barrington‐Leigh et al .…”
Section: Introductionmentioning
confidence: 98%
“…This halo is interpreted as arising from electrostatic stress by lightning [ Barrington‐Leigh et al , 2001]. Bering et al [2004] have recently found the occurrence of numerous halos associated with negative CG lightning discharges. This circumstance may produce a possible explanation for the sprite polarity paradox, which is the reason why Williams et al [2007] have mentioned this halo as the dark horse in the race to understand TLEs.…”
Section: Introductionmentioning
confidence: 99%
“…Much uncertainty exists about the generation mechanism of sprites, with several theories in contention, however most theories require the existence of large electric field transients in the mesosphere and ionosphere for sprite formation, hence measurement of electric fields at these high altitudes is a motivation for current research. Several large campaigns have attempted to measure electric fields above TLE producing thunderstorms including campaigns in 1999 (Bering et al 2004a;2004b), 2002(Thomas et al 2009Holzworth et al 2005(Sao Sabbas et al 2010. Electric field instrumentation typically comprises three orthogonal double Langmuir probes to measure ac and dc vector electric fields (basic description is given in section 3.1.1), flown on a balloon platform (see e.g.…”
Section: Above Storm Topsmentioning
confidence: 99%